The frontier of digital opportunity: Smart city implementation in small, rural and remote communities in Canada. (February 2021) - Spicer, Zachary; Goodman, Nicole; Olmstead, Nathan
Studies of 'smart cities' in Canada primarily focus on large cities but not small, rural and remote communities. As a result, we have a limited understanding of the incentive structures for smaller, remote and rural communities to pursue smart city development. This knowledge deficit is concerning, since the introduction of technology can hold a number of unique benefits for these communities, including easier connections to the rest of Canada and large urban centres, reputation building, improved service delivery and enhanced opportunities for residents. Drawing upon localised forms of knowledge creation, policy development theories, adoption and local competition literature and primary interviews with private and public officials, we examine the challenges and opportunities of 'smart city' implementation through case studies of small and rural municipalities in Annapolis Valley in Nova Scotia and a remote community, Iqaluit, Nunavut. We find that collaboration is essential for rural and remote pursuit of smart city development and is necessary to counteract the limitations of capacity, scale and digital divides. Challenges aside, however, the primary rationale for adoption of smart city technology remains the same regardless of size: enhanced quality of life for residents and sustained community health.